A Study of Tender Offer Buyback and its Share Price Performance in India - Varma, Urvashi; Munjal, Alka (Indian Journal of Finance, 2016)
Almost 90% of the 54 public announcements for tender offer buyback between 2004 to 2013 suggested that their primary need for buyback is to increase the overall shareholder value for long term shareholders. The other important drivers are capital structure correction, improvement of earnings per share through buyback, effective utilization of surplus cash, and improvement in return ratios like return on net worth and return on asset. The study tried to investigate using a sample of 54 companies the significant drives using discriminant analysis for tender offer repurchase in India. Capital structure correction is the most significant driver for tender offer buybacks in the study. The paper also deployed the event study mechanism to see if there was any change in the share price onÂ the day of the buyback announcement. The abnormal return calculated using market model indicated a positive reaction of the market on the day next to buyback announcement and reemphasised that companies are able to create value for their shareholders through tender offer share buyback.